Factors Affecting the Academic Performance of Postgraduate Nursing Students in Selected Universities in Pakistan - Kouser, Saima (2023)
A key factor in the advancement of the nursing profession is nursing education. It helps nurses develop their leadership and management abilities, giving them the chance to take on managerial and administrative responsibilities in healthcare institutions. Nursing students in Pakistan face a unique set of challenges that can impact their academic performance. An Explanatory Sequential Mix-Method study design was used to investigate the interplay of various factors that affect the academic performance of postgraduate nursing students in the selected universities in Pakistan. Building upon the exploration of factors influencing educational grades, this study further inquire strategies to address and mitigate the challenges faced by nursing students. Six medical/health sciences universities in three of Pakistan's province capital cities provided the data. 230 Masters nursing students completed an adopted questionnaire about the challenges faced by postgraduate nursing students. Academic performance was assessed using standards established by Pakistan's Higher Education Commission. Qualitative data was collected by interviewing 12 informants; an interview guide was used. Students’ demographics were calculated by Mean and + SD. The grading point means differences of postgrad nursing students with demographic factors and the impact of student, institution, and supervisor factors nursing student’s grades were computed by ANOVA and t-test. Significance in differences concerning age group was calculated by the Posthoc Tukey test. The relationship between demographics and students, institutional, and supervisor factors was estimated by Pearson correlation. The best predictors among four factors were identified by multiple regression analysis. Thematic analysis was carried out for qualitative data analysis. Key findings of the study indicate a significant mean difference in the academic performance of nursing students and financial support. Furthermore, employment status is found to be the best predictor amongst all student-related factors. Moreover, the qualitative findings of this study are also considerably matched with the results of quantitative analysis as qualitative data collected on the factors affecting students’ academic performance during in-depth-interviews is contextualizing quantitative results. By identifying the challenges faced by this unique student population and interventional strategies, current study provides valuable insights that can inform educational organizations, Government and faculty members. This can lead to the the creation of a more supportive and enriching learning environment for postgraduate nursing students.